Sonophotolytically Synthesized Silicon Nanoparticle‐Polymer Composite Ink from a Commercially Available Lower Silane. Issue 15 (20th June 2016) - Cádiz Bedini, Andrew P.; Muthmann, Stefan; Flohre, Jan; Thiele, Björn; Willbold, Sabine; Carius, Reinhard
Abstract : The preparation of a printable silicon ink using semiconductor grade and commercially available trisilane (Si3 H8 ) is reported. The synthesis is carried out in solution at room temperature or below in N2 atmosphere at ambient pressure and involves an initial sonication step, followed by irradiation with ultraviolet light. The production of higher order silanes via ultrasound using gas chromatography is demonstrated and nuclear magnetic resonance measurements are used to show that a combined sonophotolytic treatment yields a highly branched silicon hydride polymer. In addition, scanning electron microscopy (SEM) images are used to ascertain the sonocatalytic production of silicon nanoparticles. Furthermore, it is argued that these particles are partially responsible for enabling dramatically accelerated polymer growth, not otherwise observed in the same amount of time using ultraviolet light alone. Finally, the utility of the ink used in this study is demonstrated for the field of printable electronics by fabricating amorphous silicon thin films by spin‐coating and atmospheric pressure chemical vapor deposition with optoelectronic properties approaching those of state‐of‐the‐art plasma enhanced chemical vapor deposition (PECVD) material. Abstract : A solution‐processed ink composed of silicon nanoparticles and a silicon hydride polymer prepared via a combination of ultrasonic irradiation and ultraviolet light using commercially available, semiconductor‐grade purity trisilane as precursor is presented. It is also shown that the ink can be used to fabricate high‐quality amorphous silicon thin films suitable for application in optoelectronic devices.